Structural fabric in Deep Sea Drilling Project cores from forearcs - Moore, J. Casey 1945- (Memoir (Geological Society of America), 1986)
Chapter 2 provides a comprehensive macroscopic and microscopic description of the cores. Chapter 1 includes tectonic overviews of the forearcs sampled by the cores and chepters 3 through 6 provide indepth studies of especially significant structural features:faults, scaly fabrics, veins and cataclastic fabrics. Chapters 7 and 8 present detailed analysis of core mineralogy and physical properties, respectively, which lead to fundamental insights into the incipient alteration of sediment in accretionary wedges.Experiments relevant to the interpretation of structural fabrics of DSDP cores constitute the subject of chapter 9. The final chapter provides a theoretical overview of deformation mechanisms operative during deformation of materials from DSDP cores, and the transition to deformation mechanisms that appear to be dominant in equivalent, more buried rocks.